Framing a Trickster Character in Two Different Media and Eras: A Study on Br’er Rabbit in Uncle Remus’ Stories and Disney’s Song of the South - Nur Saktiningrum (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2017)
This article analyses Br’er Rabbit, a trickster character in African-American folklore. As a trickster Br’er Rabbit possesses a paradoxical nature. On the one hand, Br’er Rabbit acts as a hero but on the other hand, he constantly plays tricks on others and by doing so, he is also violating the prevailing values. These two opposing aspects of trickster’s nature offer an interesting subject for the research. The questions considered worth focusing on in discussing the subject are: How can trickster character be described? What values are represented by trickster character? Is there any shift in the description and represented values in different media and over time? The study presented in this article was aimed at investigating the transformation of how the trickster is characterized and values represented by trickster Br’er Rabbit in Uncle Remus’ folktale version of “The Wonderful Tar Baby (1881) and The Laughing Place” (1903) written by Joel Chandler Harries and the same trickster character in the same stories featured in Disney’s “Song of the South” (1946). By comparing and contrasting both narratives in different media and eras, it is uncovered that there are some changes on the depiction and nature as well as values represented by Br’er Rabbit, the trickster character. The study presented in this article was aimed at investigating the transformation of values represented by trickster Br’er Rabbit in Uncle Remus’ folktale version of “Tar Baby and The Laughing Place” (1879) written by Joel Chandler Harries and the same trickster character in the same stories featured in Disney’s “Song of the South.” The research questions of this study are answered by applying Barths’ theory and method in studying headlines news. This model of research enables the researcher to understand and interprete values represented by the trickster character in different times and media.